Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex - Zea, Sven; López-Victoria, Mateo (Zootaxa, 2016)
Several groups of sponges are able to excavate galleries and tunnels in calcareous substrata such as limestone rock, shells, calcareous algae and coral skeletons. Within the genus Cliona, some species share the common traits of being brown to olive-green in color, and harboring photosynthetic, unicellular dinoflagellates (zooxanthellae). These Cliona spp. have been grouped as the Cliona viridis species complex. Several species of this complex completely encrust the excavated substratum with a thin veneer of tissue and, when colonizing dead exposed parts of live coral colonies, they are able to undermine or overgrow and thus kill live coral tissue as they advance predominantly laterally. In the course of our taxonomic and ecological studies of Caribbean brown to brown-black encrusting Cliona, we found an as yet undescribed species that stands out by having tylostyle megasclere spicules with narrow heads and lacking the usual microsclere spicule complement of spirasters. This species, named and described here Cliona acephala n. sp., has so far been found exclusively in the Santa Marta area, Caribbean coast of Colombia. Previous studies with ITS2 ribosomal DNA showed it to be genetically distinct from other Caribbean encrusting species belonging to the Cliona viridis species complex, vis. Cliona aprica, Cliona caribbaea, Cliona tenuis and Cliona varians, but making it genetically closer to Indo-Pacific Cliona orientalis. An intriguing possibility, to be addressed with further studies, is that C. acephala n. sp. may have been introduced to the Caribbean. However, until proved otherwise, we regard the material presently described as distinct.